Alpha-Calcitonin Gene-Related Peptide Can Reverse The Catabolic Influence Of UHMWPE Particles On RANKL Expression In Primary Human Osteoblasts - Kauther, Max D. (Ivyspring International Publisher, 2010)
Background and purpose: A linkage between the neurotransmitter alpha-calcitonin gene-related peptide (alpha-CGRP) and particle-induced osteolysis has been shown previously. The suggested osteoprotective influence of alpha-CGRP on the catabolic effects of ultra-high molecular weight polyethylene (UHMWPE) particles is analyzed in this study in primary human osteoblasts. Methods: Primary human osteoblasts were stimulated by UHMWPE particles (cell/particle ratios 1:100 and 1:500) and different doses of alpha-CGRP (10(-7 )M, 10(-9 )M, 10(-11 )M). Receptor activator of nuclear factor-κB ligand (RANKL) and osteoprotegerin (OPG) mRNA expression and protein levels were measured by RT-PCR and Western blot. Results: Particle stimulation leads to a significant dose-dependent increase of RANKL mRNA in both cell-particle ratios and a significant down-regulation of OPG mRNA in cell-particle concentrations of 1:500. A significant depression of alkaline phosphatase was found due to particle stimulation. Alpha-CGRP in all tested concentrations showed a significant depressive effect on the expression of RANKL mRNA in primary human osteoblasts under particle stimulation. Comparable reactions of RANKL protein levels due to particles and alpha-CGRP were found by Western blot analysis. In cell-particle ratios of 1:100 after 24 hours the osteoprotective influence of alpha-CGRP reversed the catabolic effects of particles on the RANKL expression. Interpretation: The in-vivo use of alpha-CGRP, which leads to down-regulated RANKL in-vitro, might inhibit the catabolic effect of particles in conditions of particle induced osteolysis.